Harmine derivative B-9-3 inhibits non-small cell lung cancer via the VEGFA/PI3K/AKT pathway - Wu, Yuche; Wang, Bing; Mao, Xuwen; Chen, Wei; Akber Aisa, Haji (Frontiers in Pharmacology, 2025)
BackgroundThis study aimed to investigate the molecular mechanism by which the Harmine derivative B-9-3 inhibits angiogenesis and promotes apoptosis in non-small cell lung cancer (NSCLC).MethodsThree non-small cell lung cancer (NSCLC) models (human NSCLC cell line A549, human lung squamous cell carcinoma cell line H226, human large cell lung carcinoma cell line H460) were established. Cell proliferation was assessed using CCK-8 assays and colony formation assays. Cell motility was evaluated through scratch wound healing, invasion, and migration assays. Cell apoptosis was analyzed by Hoechst 33258 staining, AO/EB fluorescence staining, and flow cytometry. Real-time PCR was used to measure the mRNA expression of B-cell lymphoma/leukemia-2 (Bcl-2), Bcl-2-associated X protein (Bax), and Caspase-3, while Western blotting was performed to assess the protein levels of vascular endothelial growth factor A (VEGFA), phosphatidylinositol 3-kinases p110 Beta (PI3K), phospho-phosphatidylinositol 3-kinases (p-PI3K), protein kinase B (AKT), phosphorylated protein kinase B (p-AKT), Bax, Bcl-2, and Caspase-3.ResultsCompared to the control group, B-9-3 (50, 100, 200 μg/mL) inhibited the growth and motility of the three types of lung cancer cells, suppressed cell invasion and migration, and promoted cell apoptosis and necrosis. The apoptosis rates in three types of non-small cell lung cancer (NSCLC) cells were significantly increased. The mRNA expressions of Bax and Caspase-3 were markedly upregulated, while that of Bcl-2 was significantly downregulated. Additionally, the protein levels of VEGFA, p-PI3K/PI3K, p-AKT/AKT, and Bcl-2 were notably reduced, whereas the protein levels of Bax and Caspase-3 were significantly elevated.ConclusionThe harmine derivative B-9-3 may exert its anti-NSCLC effects by inhibiting angiogenesis and promoting lung cancer cell apoptosis via the VEGFA/PI3K/AKT signaling pathway.